Efficacy and acceptability of lurasidone for bipolar depression: a systematic review and dose–response meta-analysis - Marco Solmi; Edward Chia-Cheng Lai; Andre F Carvalho; Yu-Kang Tu; Pao-Yen Lin; Ping-Tao Tseng; Chih-Wei Hsu; Chih-Sung Liang; Kuo-Chuan Hung; Eduard Vieta; Yu-Wei Lin; Yang-Chieh Brian Chen (BMJ Mental Health)
Question The optimal dose of lurasidone for bipolar depression is unclear. This study examined its dose–response relationship for efficacy, acceptability, and metabolic/endocrine profiles.Study selection and analysis Five databases and grey literature published until 1 August 2024, were systematically reviewed. The outcomes included efficacy (changes in depression, anxiety, clinical global impression, disability and quality of life), acceptability (dropout, manic switch, suicidality and side effects) and metabolic/endocrine profiles (changes in body weight, glucose, lipid and prolactin levels). Effect sizes were calculated using a one-step dose–response meta-analysis, expressed as standardised mean differences (SMDs), risk ratios (RRs) and mean differences (MDs) with 95% CIs.Findings Five randomised clinical trials (2032 patients, mean treatment duration 6 weeks) indicated that the optimal therapeutic dose of lurasidone (40–60 mg) improved depression (50 mg: SMD −0.60 (95% CI −0.30, –0.89)), anxiety (50 mg: −0.32 (95% CI −0.21, –0.42)), clinical global impression (50 mg: −0.67 (95% CI −0.30, –1.03)) and disability (50 mg: −0.38 (95% CI −0.08, –0.69)). Side effects increased with higher doses (50 mg: RR 1.15 (95% CI 1.05, 1.25); 100 mg: 1.18 (95% CI 1.02, 1.36)), but dropout, manic switch and suicidality did not show a dose–effect relationship. Weight increased at doses<60 mg (40 mg: MD 0.38 (95% CI 0.16, 0.60) kg), while blood glucose levels rose at doses>70 mg (100 mg: 3.16 (95% CI 0.76, 5.57) mg/dL). Prolactin levels increased in both males (50 mg: 3.21 (95% CI 1.59, 4.84) ng/mL; 100 mg: 5.61 (95% CI 2.42, 8.81)) and females (50 mg: 6.64 (95% CI 3.50, 9.78); 100 mg: 5.33 (95% CI 0.67, 10.00)).Conclusions A daily dose of 40–60 mg of lurasidone is a reasonable choice for bipolar depression treatment.Trial registration number INPLASY202430069.